Developmental aspects of mood disorders. - Lau, J (2013)
Rates of depression double in the transition to adolescence. Symptoms of depression in adolescence also predict adult mood disorders. From a preventative perspective, research into the risk factors for adolescent depression is critical. Simultaneously, there is also growing interest in understanding why adolescence reflects a particularly critical period for the onset of early mood symptoms. Here, we review (a) the role of social, genetic, neural and cognitive factors in explaining individual differences in the propensity to develop symptoms in adolescence, and (b) whether changes in these factors may explain why adolescence is a particularly sensitive period for the onset of depressive symptoms. Finally, we speculate on whether novel social stressors interact with 'genetic innovation' to produce changes in brain circuitry structure and function and associated changes in emotion regulation abilities and social understanding-to increase emergence of symptoms in adolescence.